STUDI TENTANG USAHA-USAHA PENINGKATAN TARAF KESEHATAN MASYARAKAT DI DESA DATAR KECAMATAN SUMBANG KABUPATEN BANYUMAS TAHUN 2009 - Dardjito, Endo; Nurcahyo, Panuwun Joko (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2010)
ABSTRACT Government continue to try to improve level health of society through various developed program. So that executed medicare in an area as according to requirement, hence have to know by various medicare which have been executed by in area. This Research aim to know various effort the make-up of public health which have been done by in Datar Countryside District Sumbang of Sub-Province of Banyumas. This type research is research of observasional with method survey and this research have the character of analytic descriptive, that is research elaborating and diging how a phenomenon happened. Population at this research do not too much, so that sampel at this research use all population, that is counted 31 cadre of Posyandu Datar Countryside District Sumbang of Sub-Province of Banyumas. Data collecting done with open interview technique, so that direct researcher note result of interview. From result of research concluded that effort the effort the make-up of health of society in Datar Countryside District Sumbang of Sub-Province of Banyumas, covering: weighing-machine of balita one month once, pregnant mother monitoring, do counselling of health, immunize at balita, executing Post of PAUD, provide facilities and basic facilities for Polindes, try to ask countryside midwife to undertake at Polindes, try to continue to develop clean aqueduct for the requirement of citizen, repair of irrigation and moats, continue to improve enableness of society in environmental keep cleaning through job devote, try to fulfill requirement of facilities and basic facilities for the activity of Posyandu, assist giving immunize at activity of Posyandu, assist activitys of counselling of health, try to fulfill requirement of facilities and basic facilities for the activity of Posyandu, assist  giving immunize at activity of Posyandu, assist activitys of counselling of health, development of moat irrigate, repair of irrigation, pipe aid for requirement of is tacking on aqueduct clear, aid making of family latrine, and appliance aid physic of education (APE). Keyword: Public health Level, Posyandu. Kesmasindo Volume 3, Nomor 1, Januari 2010, hlm. 76-85